Addressing health inequities in Bologna: a mixed-method, multi stakeholder, action-research approach. (30th September 2020) - Bodini, C; Camplone, I; Cavazza, G; Di Girolamo, C; Gentilini, V; Marzaroli, P; Pandolfi, P; Perlangeli, V; Pizzi, L; Riccio, M
Abstract: Background: A large body of literature shows how lower socioeconomic classes have higher incidence of mortality and morbidity, and how worse health outcomes linked to barriers in accessing healthcare particularly affect the most vulnerable groups. Despite such evidence, in many a context health inequalities have continued to increase. Processes that better link knowledge with action are therefore needed. Methods: An interdisciplinary, interprofessional, interinstitutional group was created involving the Public Health Department and the Center of International Health of Bologna. In 2017-19, the group carried out a project to document and tackle local health inequities, structured in two phases: a first one of quantitative analysis of health inequalities using routinely available data, and a second one of qualitative research in selected areas of the city. An action-research approach was embedded throughout the project, with periodic evaluations to ensure progress towards the intended results. Results: Phase 1 results show significant differences in terms of disease burden and service use between the North, East and West periphery of the city compared to the center and South. These differences mirror the urban distribution of wealth/deprivation, measured through different indicators (education, income, presence of immigrant population). Results also show concentration of the worst health outcomes and healthcare access indicators in some areas of the city, which also have higher presence of social housing. Phase 2, started in January 2020, is using phase 1 results to inform both a qualitative analysis and a participatory process in 6 areas of the city selected among those with worst health indicators. Conclusions: Our experience shows that addressing the issue of health inequities through a mixed-method, multi stakeholder and action-research approach may lead to greater integration of research findings and evidence into healthcare policy and practice, towards health equity. Key messages: Working across disciplines, roles and institutions may bring added value to the complex field of health inequities, when approached with the aim of moving from knowledge to action. Relying on routinely available data may open a route for the replication of our experience and for its use to monitor the impact of interventions aimed at reducing health inequities.